Budgetary Slack Ditinjau Dari Partisipasi Penganggaran Dengan Komitmen Organisasi Dan Budaya Organisasi Sebagai Variabel Moderasi Studi Pada Lembaga Non Profit - Zubizaretta, Kevin Aridya; , Drs. Eko Sugiyanto, M.Si (2016)
The purpose of this study was to determine the extent of organizational commitment and organizational culture moderates the effect of budget participation on budgetary slack. This study uses empirical studies using surveys. The population in this study is a manager at a non-profit institution that is in the region of Ex Hospital Surakarta. Samples are middle managers in Hospitals in the region Surakarta Ex. The sample was taken by purposive sampling technique. The data obtained from questionnaires required. Data were analyzed using classical assumption test and multiple regression analysis, t test, F test, and test the coefficient of determination. The results showed that: (1) Participation budgeting negatively affect budgetary slack. The results of the regression analysis obtained a value of p = 0.004 is accepted at significance level of 5%. This means that the participation of the budget will decrease the possibility of budgetary slack; (2) The interaction of budgetary participation and organizational commitment negatively affect budgetary slack. Results of regression analysis to obtain the p-value for interaction participation and organizational commitment of 0.014 accepted at significance level of 5%. This means that the participation of the budget will decrease the budgetary slack when subordinates committed high organization; (3) Interaction budgetary participation and organizational culture does not affect the budgetary slack. Results of regression analysis to obtain the p-value for interaction participation and organizational culture of .458 rejected at the 5% significance level.